2017
DOI: 10.3892/ol.2017.7587
|View full text |Cite
|
Sign up to set email alerts
|

The effects of hemocyanin on T cells cultured in�vitro

Abstract: Abstract. As a broad-spectrum antibiotic, gentamicin is used extensively in T cell culturing in vitro, but preliminary studies have identified that T cell activity is significantly affected by gentamicin. In the present study, the hemocyanin from Litopenaeus vannamei (L. vannamei) was selected as an additive for T cell cultures in vitro. Compared with those in the control group, the cell quantity exhibited no significant difference, and the formation rate of cell colony increased gradually with increases in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Activated AKT inturn phosphorylates the downstream molecules PDK1 and mTOR, which on further activates the transcription factors responsible for the cell survival, growth and proliferation. [37] AKT inhibitor GDC 0068 and mTOR inhibitor RAD-001 are currently used to treat lung cancer patients in phase I trial, [38] which has severe side effects. In the present study, dieckol a herbal based drug with nil side effects effectively inhibited the PI3K/AKT/mTOR signaling pathway and it also significantly decreased the expression of P70S6K and the transcription factor cyclin D1 which confirms dieckol as potent anticancer agent induces apoptosis via inhibiting PI3K/AKT/mTOR signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Activated AKT inturn phosphorylates the downstream molecules PDK1 and mTOR, which on further activates the transcription factors responsible for the cell survival, growth and proliferation. [37] AKT inhibitor GDC 0068 and mTOR inhibitor RAD-001 are currently used to treat lung cancer patients in phase I trial, [38] which has severe side effects. In the present study, dieckol a herbal based drug with nil side effects effectively inhibited the PI3K/AKT/mTOR signaling pathway and it also significantly decreased the expression of P70S6K and the transcription factor cyclin D1 which confirms dieckol as potent anticancer agent induces apoptosis via inhibiting PI3K/AKT/mTOR signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…These materials leverage their supramolecular or self‐assembly capabilities to interact with perovskite, effectively enhancing the stability of perovskite solar cells in various aspects, such as releasing residual lattice strain, suppressing ion migration, passivating defects, and improving moisture resistance. [ 152–154 ] For instance, Wei et al. introduced a new type of chelation‐like cation–π interaction into PSCs by incorporating aromatic rubrene into perovskite films during the film‐forming process, thereby restricting the migration of organic cations.…”
Section: Auxiliary Self‐healing Behaviormentioning
confidence: 99%
“…discovered that the self‐assembly of amine nickel porphyrins can release residual lattice strain, thereby inhibiting the phase transition of perovskite films under prolonged illumination conditions. [ 152 ] XRD results revealed that the crystalline peak of the doped perovskite film (001) showed a smaller angle shift compared to the undoped perovskite film after 12 h of illumination.…”
Section: Auxiliary Self‐healing Behaviormentioning
confidence: 99%
“…As an aldotetrose, it contains three hydroxyl groups and the hemiacetal group or the aldehyde group. This monosaccharide is of biological importance, [34][35][36][37][38][39] and as C 4 sugar erythrose is of potential astrobiological relevance. In the water solution, the equilibrium percentage concentration ratio of the a-furanose to the b-furanose to the open-chain tautomers of D-erythrose was established by NMR spectroscopy to be 25:65:12, [8] indicating the dominance of the cyclic tautomers.…”
Section: Introductionmentioning
confidence: 99%